GC-MS Analysis of the in vitro leaf derived Callus Extracts of Ichnocarpus frutescens (L)W.T.Aiton: Life Sciences-Botany - Ashwini; Rajanna, L. (International Journal of Life Science and Pharma Research, 2022)
Medicinal plants are the treasure house of secondary metabolites. Production of seconmdary metabolites through micro propagation technology has immense application in new drug discoveries. Ichnocarpus frutescens (L.) W.T. Aiton - is a latex secreting medicinal herb commonly known as black creeper or Krishna Sariva belonging to the family Apocyanaceae.The present study was aimed at induction of callus from the leaf explants of I. frutescens using Murashige and Skoog (MS) medium supplemented with various combinations of plant growth regulators. Maximum amount of green compact mass of callus was proliferated from leaf explants on MS medium fortified with 3mg/L NAA + 2mg/L BAP. The main objective of the present study was to investigate the secondary metabolites in different extracts of callus by GC-MS analysis. To our best knowledge, no literature is available and this is the first report on GC–MS analysis of leaf derived callus extracts, which showed the presence of different phytocompounds out of which, Stigmasterol, Hexadecanoic acid, Beta-Sitosterol, Stigmasta-3,5-dien-7-one and Heptacosane are the major compounds that found to possess a wide range of biological activities. This protocol could be used to identify the secondary metabolites from leaf derived callus of the I. frutescens and further studies have to be carried out for the isolation and characterization of novel compounds for the formulation of new pharmaceutical drugs and also for its commercial production which will be used to cure some important ailments. ,